Return of the Jew Identity Narratives of the Third Post-Holocaust Generation of Jews in Poland - Reszke, Katka (Jews of Poland, 2013)
A new, "unexpected" generation of Jews made an appearance in Poland following the fall of the communist regime. Once home to the greatest Jewish community in the world and then site of one of the biggest tragedies in Jewish history, today Poland is experiencing what some have called a "renaissance of Jewish culture." Simultaneously, more and more Poles are discovering their Jewish roots and beginning to seek forms of Jewish affiliation. Can there be "authentic" Jewish life in Poland after fifty years of oppression? "Return of the Jew" offers the first in-depth study of the third post-Holocaust generation of Jews in Poland. It provides a revealing account of the experience of being or rather becoming Jewish vis-a-vis uniquely compelling circumstances.